“We thought we were stronger than we were”: adopters’ narratives about the adoption journey and disruption - Bejenaru, Anca; Raiu, Sergiu; Iovu, Mihai; Negoescu, Alina; Corman, Sorina (Frontiers in Psychology, 2024)
Introduction Although the majority of adoptive families remain stable, some of them break up prematurely. Methods Adopting a qualitative approach, this study gave voice to seven adoption applicants who began the adoption journey with one or more children but did not complete the legal process. Our goal was to understand their experiences throughout the adoption process and disruption. Results The results show how adoption applicants went, in a short period, from the excitement of finding a child or sibling group to disillusionment and trauma. The main risk factors that hinder adoption stability include unrealistic expectations, intuitive choice of the child in the absence of accurate information, challenges posed by the child’s particular characteristics, and lack of professional support. Discussion Our study highlights the need for adopters to be assisted throughout the entire process by specialists, to be better prepared to deal with the complex needs of children in the protection system, and to facilitate their access to a complex of specialized services to meet the different needs of every family.